Analisis Hubungan Pergaulan dengan Teman dan Paparan Media Pornografi terhadap Perilaku Seksual Pranikah pada Remaja - A.C Dimas Pratama; Hari Basuki Notobroto (Universitas Airlangga, 2017)
There are internal factors and external factor affect to adolescent premarital sex. There were 60% adolescent who have imagine sexual intercourse, and 50% adolescent have access porn sites on the internet, and 40% adolescent have negative effect of sexual attitude from environment. This research was an analytic research that used cross sectional study and use quantitative approaches derived from primary data by disseminated a questionnaire. The population were students from grade X and XI 10th Vocational High Schools State Of Surabaya. Sample was taken with simple random sampling about 89 students. Data analyze this research used Spearman Correlate Coefficient test . Variables in this research was media exposure of pornography and peer behavior effect. There were correlate between them. Variables “peer behavior effect from friend” has association with premarital sexual behavior,media exposure of pornography also has association too (p = 0.000). Cooperation between school, parent and government institution must regulate the education system about reproductive health for students especially about premarital sexual behavior for teens. Parent should give more intention to maintain good relations and monitored their children.